SIMULATION STUDY OF A CONTINUOUS FERMENTER USING IMMOBILIZED CELLS - Palomino-Infante, A. (1999)
This work aims to simulate a bioreactor to produce ethanol from glucose using immobilized cells . First, we have proceeded to statistically evaluate the proposed kinetic models , from which we selected the model Aiba , Shoda and Nagathani [18 ] as the most appropriate model . Second, the values ​​of the simulated fermentation have been validated by comparing the results with experimental data and Mutharasan Gencer [17 ] . Finally , the yield of ethanol production was simulated by considering a bioreactor of PFR type . The solution of the equations of material balance was done using Runge Kutta algorithm in Mathcad 7P IV . Comparison of simulated and experimental Mutharasan Gencer sample values ​​appropriate arrangement .